Daughters of God - Chai, Jac-Quinn (2012)
“Daughters of God” is a documentary about a Hindu temple built by Thirunankais (Indian transsexuals) in Malaysia. It is a story that focuses on two Thirunankais- Anusha and Varsha, who attend the temple during days of prayers but roam the streets as prostitutes at night. The temple is funded by only the Thirunankais, and a majority of them work in the same profession. Despite being different in terms of their gender and their choice of livelihood, through the presence of the temple, the Thirunankais have gradually gained acceptance of the people living in the neighbourhood.